STRATEGI PENGELOLAAN HUTAN LINDUNG ANGKE KAPUK - Dwi Agus Sasongko; Cecep Kusmana; Hikmat Ramadan (Graduate School Bogor Agricultural University (SPs IPB), 2014)
Angke Kapuk Protected Forest (AKPF) which is formed by mangroves has many important benefits for environment. AKPF, as implied in Master Plan of Jakarta City (RTRW DKI Jakarta) serve as a guarded and protected area. AKPF condition which is more threatened needs strategic policy in management. Accordingly, this research was aimed to identify and analyze AKPF internal-external factors and to arrange AKPF management strategies. Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) are used for identifying and analyzing AKPF internal-external factors. SWOT Matrix and QSPM are used for arranging management strategies and its priority.AKPF internal factors are strengths and weaknesses. AKPF external factors are opportunities and threats. Evaluation result shows, that AKPF internal factors have a score of 2.15. AKPF has not fully received the benefits for its strength. On the other hand, AKPF is greatly influenced by its weakness. AKPF external factors have a score of 2.20. According to the score, AKPFhas not received benefits from the various opportunities that exist. On the other hand, AKPFis still weak in the face of dynamic external environment. There are eight management strategies for AKPF, in which mangrove rehabilitation is the main priority. Keywords: AKPF, external factors, internal factors, management strategy